The power of images: re-examining the wall paintings from the Throne Room at Knossos - Galanakēs, Iōannēs; Tsitsa, Efi; Günkel-Maschek, Ute (The annual of the British School at Athens, 2017)
The aim of this paper is to re-examine the painted fragments discovered by Arthur Evans and his team in the Throne Room at Knossos in 1900. We have tried to integrate systematically the extant archival data stored in the Ashmolean Museum in Oxford and the archaeological remains at Herakleion in an attempt to retrace the history of discovery of the paintings. In our view, the iconography of this programme places its execution at the onset of Late Minoan (LM) II. We see the inclusion of both ‘traditional’ (Neopalatial) and ‘innovative’ (Final Palatial) elements in the composition as suggestive of an attempt on behalf of the artist(s) and the commissioner(s) to blend artistic traditions in the creation of a new, yet still recognisable, image of power. We assess the implications stemming from this suggestion and interpret the decorative programme of the Throne Room at Knossos as part and expression of the emergence of the wanax ideology